Aid, trade and migration: How do bilateral flows interact?. (13th September 2017) - Menard, Audrey; Gary, Aurore
Abstract: This paper takes as its point of departure the European Commission's position, set out in 2005, which laid clear emphasis on aid and trade as tools for controlling immigration. We attempt to subject this position to empirical investigation. We exploit data on bilateral aid, trade and migration flows between developed and developing countries, for the period 2000–10, adopting an instrumental variable approach to address the endogeneity issue due to potential simultaneity bias. Our results establish that increasing aid and trade with developing countries is likely to fail to contain immigration, at least in the short run. The pattern of results is consistent with the hypothesis that promoting development in migrant‐sending countries, or cooperating with such countries to control migration outflows, is not sufficient to lessen immigration. Increasing visa restrictions and controls at borders is generally controversial; still, the results imply that policymakers cannot attain their short‐term immigration goals with the so‐called smart solutions of aid and trade.